Muslim Perspective of Western thought on Human Nature: A Study of Muhammad Rafī-ud-Dīn’s Discourse (Al-Qamar, 2021)
This paper is a study of the thoughts of Dr. Muhammad Rafī-ud-Dīn (1904-1969), a prominent Muslim theorist and philosopher of subcontinent, about human nature and his refutation of Western thinkers on the subject. It finds that modern world view and episteme do not consider Man as the crown amongst all the creations. All the eminent Western psychologists and writers on Human Nature agree that man possesses an urge for ideals which is responsible for his all kinds of activities. According to Freud it is the sexual instinct, Adler relates this urge to the self-assertion and ego, McDougall thinks it the outcome of a combination of all the instincts. Karl Marx reveals that ideals are rooted in the economic urge of man while Darwin already had declared Man as a result of an automatic evolutionary process. These theories had played an important role in creating the world view or weltanschauung of the man of 20th century. But this explanation of Human Nature has deprived Man from his classical position of spirituality and morality and has depicted him as a social animal that is driven by his instincts consciously or unconsciously. The Qur’ānic concept of Human Nature as explained by Dr. Muhammad Rafī-ud-Dīn proves that the urge for ideals is the real, the ultimate and the sole dynamic power of human actions and it find its roots not in instincts but in something transcendent and metaphysical.
Keywords: Human nature; Western thoughts; Rafī-ud-Dīn